Strategic Partnership Between Universities and The Private Sector to Support Entrepreneurial Project: Kemitraan Strategis antara Universitas dan Sektor Swasta untuk Mendukung Proyek Kewirausahaan - Al-Sabaawe, Younis Mohammad; Albayati, Nashwan Hamdi Hussein; Al-Obaidy, Narmeen AbdulRazzaq Saleh (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Universities are pivotal in fostering economic development through their role in scientific research and innovation. Specific Background: In Iraq and other developing contexts, the synergy between universities and the private sector remains underdeveloped, limiting the impact of academic research on entrepreneurial advancement. Knowledge Gap: Despite growing attention to research incubators globally, there is a lack of comprehensive models tailored to integrate them effectively within Iraqi universities. Aims: This study proposes a structured model for implementing research business incubators aimed at enhancing strategic university–industry cooperation and supporting entrepreneurial ventures. Results: The findings reveal that Iraqi universities possess the foundational capacities necessary for incubator implementation, including human capital and organizational readiness, though these elements require systematic integration and strategic planning. Novelty: The proposed model introduces a three-phase framework—principles, mechanisms, and supportive requirements—grounded in process management theory, offering a scalable roadmap adaptable to local contexts. Implications: This research informs university policymakers and private stakeholders on how to establish collaborative incubator systems that drive innovation, reduce graduate unemployment, and align research outputs with societal and economic needs.Highlight: Strategic cooperation between universities and the private sector enhances innovation and community impact. Research incubators offer a structured process to transform academic research into viable entrepreneurial ventures. Three-phase model (principles, mechanisms, support) ensures effective and sustainable implementation of incubators. Keywords: Strategic Cooperation, Research Incubators, Entrepreneurial Projects, University Partnerships, Private Sector